An information system for the management of forest fires - Sphyris, Angelos (BOIS & FORETS DES TROPIQUES, 2001)
Le résumé en français est disponible dans le fichier PDF de l'article. A short tour of FMIS (Fire Management Information System) is presented. Its prime functions, relating to fire prevention, behavior estimation and suppression coordination are described and screenshots of various stages in the use of the system accompany the text to aid understanding. (Résumé d'auteur)